Analisis Rasio Likuiditas Terhadap Profitabilitas Pada Perusahaan-Perusahaan Yang Terdaftar di Jakarta Islamic Index Periode 2017-2022 - Salsabila Eka Sutrisna; Djatnika, Djoni (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Based on the data obtained that there is a difference in fluctuations between the average amount of revenue and net profit of companies listed on the Jakarta Islamic Index. When observed from a capital perspective, the average yield shows that the company chooses to fund its operations with a larger proportion of capital than liabilities. This study aims to analyze how far the influence of the liquidity ratio on profitability in companies listed on the Jakarta Islamic Index. The results of the study show that the current ratio, cash ratio, quick ratio and working capital to total assets do not affect return on assets simultaneously. The current ratio has no effect on return on assets partially. Cash ratio has no effect on return on assets partially. Quick ratio has no partial effect on return on assets Working Capital to Total Asset has no partial effect on return on assets